Newly diagnosed Glioblastoma Multiforme (GBM) during COVID-19 pandemic: changes in therapeutic approach to minimize in-hospital SARS-COV-2 contagion in pre-vaccine era - Internò, Valeria; Rudà, Roberta; Sergi, Maria Chiara; Soffietti, Riccardo; Porta, Camillo (Acta Biomedica Atenei Parmensis, 2022)
COVID-19 pandemic revolutionized the way in which cancer patients are treated worldwide. Regarding neuro-oncological patients, usually considered frail and with lower life-expectancy in respect to other oncological patients, the international scientific community had to urgently reorganize the treatment approach in order to minimize the risk of in-hospital contagious. For GBM patients, adjuvant treatments have been evaluated with even much more attention with regard to the expected efficacy. As a consequence, an hypofractioned radiotherapy regimen has been preferred in order to reduce the daily hospital accesses and, especially in pMGMT unmethylated patients, chemotherapy with Temozolomide was avoided. Here, we made a comprehensive evaluation of the neurooncological community suggestions regarding GBM treatment in the pre-vaccine era of COVID-19 pandemic.